Amodal Presence and the Bounce/Stream Illusion. (August 2018) - Anstis, Stuart
Ambiguous bounce/stream collision points were hidden behind an occluder so that observers had to complete them amodally. In Movie 1, straight or curved static lines were painted on the occluder. In Movie 2, dotted textures flowed in straight or curved lines across the front of the occluder. In Movie 3, moving eyes, painted on the occluder, either moved in straight lines, as if tracking streaming spots, or else followed curved paths, as if tracking bouncing spots. The straight (or curved) lines, texture flow or eye movements led to judgments of streaming (or bouncing). These effects demonstrate the role of attention and expectations in disambiguating bounce/stream stimuli.